2008
DOI: 10.1007/s10653-008-9175-8
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns of non-carpeted floor dust loading in Syracuse, New York (USA) homes

Abstract: Residential floor dust loading was measured on the smooth floor surface of 488 houses in Syracuse, New York, during the summers of 2003 and 2004. Using U.S. Environmental Protection Agency (EPA) wipe methods, pre-weighed Ghost Wipes, Lead Wipes, or Whatman Filters were employed to collect duplicate samples from (predominantly) kitchens. The collection efficiency of the various media was determined from multiple wipe tests and side-by-side comparisons. The results were normalized and aggregated at the census tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
(16 reference statements)
1
16
0
Order By: Relevance
“…Kuo et al 24 had shown the average household dust loadings in Taiwanese households were 0.0603 and 0.0382 mg/m 2 for exposure and control site, respectively. These were an order of magnitude smaller than the household dust loadings measured in the US homes [31][32][33] (geometric means were 0.28-0.42 g/m 2 ). This is because in Taiwan and most other Asian countries residents usually take off their shoes before entering their home.…”
Section: Discussionmentioning
confidence: 65%
“…Kuo et al 24 had shown the average household dust loadings in Taiwanese households were 0.0603 and 0.0382 mg/m 2 for exposure and control site, respectively. These were an order of magnitude smaller than the household dust loadings measured in the US homes [31][32][33] (geometric means were 0.28-0.42 g/m 2 ). This is because in Taiwan and most other Asian countries residents usually take off their shoes before entering their home.…”
Section: Discussionmentioning
confidence: 65%
“…However, in cases where an occupant does not frequently clean their flooring, multilayer deposits may form, as may be the case for some of the higher dust loads reported in Table 1, including values reported by EPA (1996), Rich et al (1999), Rao et al (2005), Lewis et al (2006), Johnson et al (2009), andHoh et al (2012). As discussed in Franke et al (1997), routine housekeeping and floor cleaning can prevent the accumulation of particles on hard flooring, maintaining dust loads below levels of 0.08 g/m 2 .…”
Section: Hard Flooringmentioning
confidence: 94%
“…Dust loads reported by Thatcher and Layton (1995), Franke et al (1997), Salares et al (2009), andRaja et al (2010) were classified as monolayer deposits. Field studies by Adgate et al (1995), Rich et al (1999), Rao et al (2005), Lewis et al (2006), Johnson et al (2009), Layton and Beamer (2009), and Hoh et al (2012 reported ranges of dust loads that likely include both monolayer and multilayer deposits. The range of dust loads can be attributed to the frequency of floor cleaning or the number of particle sources indoors, among other factors.…”
Section: Hard Flooringmentioning
confidence: 99%
See 1 more Smart Citation
“…With a subset of these results, values reported by Yiin et al (2000) indicate the ratio, R rt to range of 11.1 during the hot season to 24-25 during cool and cold periods; again, the GSD values for the measures were approximately 3.0. For the soil and dust study in Syracuse, NY, (Johnson et al 2005(Johnson et al , 2008 98 vacuum cleaner dust samples were collected from 61 different households during the summers of 2003 and 2004 by the method of Watt et al (1983). The GM value of R rt for those 61 residences was 11.3 (3.6-36, at GSD of 0.5).…”
Section: Model Performance Metricmentioning
confidence: 99%